2003
DOI: 10.1637/7028
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined Effects of the Fusarium Mycotoxins Fumonisin B1and Moniliformin in Broiler Chicks

Abstract: The individual and combined effects of feeding fumonisin B1 (FB1; 0, 100, 200 mg FB1/kg) and moniliformin (M; 0, 100, 200 mg M/kg) were evaluated using a 3 x 3 factorial arrangement of treatments. Significant mortality (P < 0.05) occurred in chicks fed all diets containing 200 mg M/kg (50%-65%). Compared with controls and chicks fed FB1, both feed intake and body weight gain were decreased (P < 0.05) in chicks fed diets containing 100 mg M/kg. Chicks fed M had heavier heart weights (P < 0.05) than control chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
(27 reference statements)
0
20
0
3
Order By: Relevance
“…The extent of the risk of feed/food co-contamination with several mycotoxins depends on the level and kind of mycotoxins, the animal kind, animal/human age and the health status, feature or organ assessed, and mycotoxins interactions can be additive, synergistic or antagonistic (Boeira, Bryce, Stewart, & Flannigan, 2000;Diaz, Squires, Julian, & Boermans, 1994;Huff, Harvey, Kubena & Rottinghaus, 1998;Kubena et al, 1997;Ledoux, Broomhead, Bermudez, & Rottinghaus, 2003;Malekinejad et al, 2007;Placinta, D'Mello, & Macdonald, 1999;Speijers & Speijers, 2004;Tajima, Schoen, Feron, & Groten, 2002). Therefore it is not possible to define safe levels of mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the risk of feed/food co-contamination with several mycotoxins depends on the level and kind of mycotoxins, the animal kind, animal/human age and the health status, feature or organ assessed, and mycotoxins interactions can be additive, synergistic or antagonistic (Boeira, Bryce, Stewart, & Flannigan, 2000;Diaz, Squires, Julian, & Boermans, 1994;Huff, Harvey, Kubena & Rottinghaus, 1998;Kubena et al, 1997;Ledoux, Broomhead, Bermudez, & Rottinghaus, 2003;Malekinejad et al, 2007;Placinta, D'Mello, & Macdonald, 1999;Speijers & Speijers, 2004;Tajima, Schoen, Feron, & Groten, 2002). Therefore it is not possible to define safe levels of mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (1999) have suggested that FB 1 is immunosuppressive in chicks when present in the ration at 200 mg FB 1 /kg diet. Moreover, combination of FB 1 and moniliforme at dosage of 200 mg/kg also induced a significant mortality, mild to moderate periportal extramedullary haematopoiesis and mild focal hepatic necrosis has been observed in chicks fed FB 1 alone (Ledoux et al 2003). There is clear evidence that fumonisins in feed or food cause animal mycotoxicosis.…”
Section: Introductionmentioning
confidence: 99%
“…The individual and combined effects of the Fusarium mycotoxins Fumonisin B1 (FB1) and moniliformin were studied in broiler chicks. The interactive effects of moniliformin and fumonisins were not synergistic; moniliformin was much more toxic to broilers than FB1 [98].…”
Section: Fumonisinsmentioning
confidence: 88%